2021
DOI: 10.3390/atmos12121547
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Estimating the Intrinsic Magnetic Field Spectrum of Kinetic-Range Turbulence

Abstract: Understanding plasma turbulence below the ion characteristic scales is one of the key open problems of solar wind physics. The bulk of our knowledge about the nature of the kinetic-scale fluctuations comes from the high-cadence measurements of the magnetic field. The spacecraft frame frequencies of the sub-ion scale fluctuations are frequently around the Nyquist frequencies of the magnetic field sampling rate. Thus, the resulting ‘measured’ time series may significantly differ from the ‘true’ ones. It follows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The median spectra show a steepening of the spectral slope near the ion spectral break (further called the kinetic range) toward the Sun. However, this evolution cannot be quantified from the median spectra because the slope can be affected by the magnetometer noise at larger distances (Pitňa et al 2021) and the part of the spectrum following the break is too short for a reliable fitting closer to the Sun. Therefore, we use the local slope determined from a full magnetic field vector which is calculated as follows.…”
Section: Spectral Slope In the Kinetic Range Of Frequenciesmentioning
confidence: 99%
“…The median spectra show a steepening of the spectral slope near the ion spectral break (further called the kinetic range) toward the Sun. However, this evolution cannot be quantified from the median spectra because the slope can be affected by the magnetometer noise at larger distances (Pitňa et al 2021) and the part of the spectrum following the break is too short for a reliable fitting closer to the Sun. Therefore, we use the local slope determined from a full magnetic field vector which is calculated as follows.…”
Section: Spectral Slope In the Kinetic Range Of Frequenciesmentioning
confidence: 99%
“…This scenario could be easily tested in spacecraft observations. Indeed, the fact that the solar wind often shows high levels of intermittency is likely the reason why the −7/3 slope is rarely observed [24,61]. Finally, multispacecraft observations (that allow direct measurement of the Hall energy transfer rate, e.g., [62]) of the pristine Hall-MHD regime would be the ideal test to confirm our findings.…”
Section: Discussionmentioning
confidence: 51%
“…In such range, the −7/3 slope is very stable in time, and lasts up to the end of the simulation, also in the decaying phase and for more than 4τ nl . Such slope is predicted by theoretical models of Hall-MHD turbulence, but it is rarely measured in spacecraft observations [22][23][24] and it has been only reported in early numerical studies of turbulence, e.g., [20,21].…”
Section: Spectral Properties and Cross-scales Energy Transfermentioning
confidence: 98%
See 1 more Smart Citation
“…where f is the frequency, c 1 and c 2 are parameters of the fit, α in corresponds to the inertial range spectral index, a tr does to the transition range, and H is the Heaviside function. In order to avoid noise effect on the analysis of magnetic field fluctuations, we follow the methodology suggested by Pitňa et al (2021b), which introduces a noise level estimated by Woodham et al (2018), and we multiply the noise floor by a factor of 5 (SNR5) as shown in Figures 2(a)-(d) (dashed-dotted green lines). This fitting method is applied in a frequency range from 0.03 to 3 Hz or to the frequency where the PSD level is equal to SNR5 if it is lower than 3 Hz.…”
Section: Magnetic Field Spectra and The Spectral Break Determinationmentioning
confidence: 99%